The impact of pulpotomy on the long-term prognosis and survival of young permanent teeth - Alshargawi, Waleed Khalid; Alsubaie, Ganem Fahaad; Altayiar, Abdullah Yahya; Alshammari, Naif Mutlaq; Aljunaidi, Shatha Abdulkhalik; Alqahtani, Saad Abdullah; Aljaffan, Sahar Mohammed; Alsulami, Luluh Ahmed; Ghazi, Reyof Mohammed; Alshabib, Zainab Yaseen; Alkabsi, Israa Yahya (International Journal Of Community Medicine And Public Health, 2023)
This review explores the impact of pulpotomies on the long-term prognosis and survival of primary and young permanent teeth. Pulpotomy is a vital pulp therapy procedure aiming to preserve pulp health and functions. The review covers various vital pulp therapy techniques, including indirect pulp treatment, direct pulp treatment, partial pulpotomy, and full pulpotomy. Apexogenesis, a procedure promoting root end formation, is also discussed. Long-term success in endodontic therapy requires an effective coronal seal to prevent microleakage and bacterial ingress into root canals. The study’s methodology involved a comprehensive literature search to gather information on pulpotomy’s effects on tooth prognosis and survival. Factors influencing the success of vital pulp therapy, such as the size of the exposure, the state of the pulp, and the choice of capping material, are analyzed. Bacterial contamination is identified as a crucial factor affecting the therapy’s prognosis. Strategies to improve pulp healing and treatment outcomes are explored, offering insights into clinical decision-making for pulpotomy procedures.